2023
DOI: 10.1002/fft2.209
|View full text |Cite
|
Sign up to set email alerts
|

The modulation effects of plant‐derived bioactive ingredients on chronic kidney disease: Focus on the gut–kidney axis

Abstract: Chronic kidney disease (CKD) results mainly from diabetes, hypertension, and glomerulonephritis, which can develop into end-stage renal disease and CKD-related complications, thereby causing high morbidity and mortality. This progression is correlated with pathogenic alterations in the gut microbiota that generate uremic toxins, mainly including indoxyl sulfate, p-cresol sulfate, and trimethylamine-N-oxide. The uremic toxins directly or indirectly induce CKD through oxidative stress, inflammatory response, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 276 publications
(292 reference statements)
0
1
0
Order By: Relevance
“…This change in gut microbiota composition subsequently induced alterations in the metabolic profiles of host, including increased SCFA production in the colon and elevated circulating levels of anti-inflammatory and antioxidative metabolites in plasma. , Moreover, anthocyanin-rich diets resulted in the enhanced excretion of specific polyphenolic metabolites in urine, indicating efficient metabolism and absorption of these beneficial bioactive compounds . Additionally, some researchers demonstrated that anthocyanin consumption in humans influenced the urinary excretion of microbial-derived metabolites, such as hippurate and p -cresol sulfate, which are considered markers of gut microbial metabolism and functionality. The observed changes in these urinary metabolites reflected the modulatory effects of dietary anthocyanins on gut microbiota and, consequently, their impact on host metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This change in gut microbiota composition subsequently induced alterations in the metabolic profiles of host, including increased SCFA production in the colon and elevated circulating levels of anti-inflammatory and antioxidative metabolites in plasma. , Moreover, anthocyanin-rich diets resulted in the enhanced excretion of specific polyphenolic metabolites in urine, indicating efficient metabolism and absorption of these beneficial bioactive compounds . Additionally, some researchers demonstrated that anthocyanin consumption in humans influenced the urinary excretion of microbial-derived metabolites, such as hippurate and p -cresol sulfate, which are considered markers of gut microbial metabolism and functionality. The observed changes in these urinary metabolites reflected the modulatory effects of dietary anthocyanins on gut microbiota and, consequently, their impact on host metabolism.…”
Section: Discussionmentioning
confidence: 99%